AUTOMATED SYSTEM OF DATA PROCESSING WITH THE IMPLEMENTATION OF RATING TECHNOLOGY OF TEACHING - О. И. Дзювина (Science and Innovation Center Publishing House, 2014)
Rating technology of teaching enables independent and individual work of students, increase their motivation. Purpose: to increase the efficiency of data processing with the implementation of rating technology of teaching. Method: analysis, synthesis,experiment. Results. Developed an automated data processing system for the implementation of rating technology of teaching. Practical implication. Education. Purchase on Elibrary.ru > Buy now